Features of Russian-Turkish and Turkish-Russian simultaneous interpretation - Abduvalieva, Gulsanam A. (Linguistics and Culture Review, 2021)
The relevance of the study lies in the fact that nowadays cooperation between countries is constantly developing at different levels, which necessitates the use of simultaneous interpreting services. In order to meet the demands of today’s market and above all to live up to the expectations, it is important to understand the special features of Russian-Turkish and Turkish-Russian simultaneous interpretation, regardless of subject matter and degree of complexity. Such interpretation is quite a complex task, since Turkish is a language belonging to the group of languages that is spoken by 83 million people worldwide, mostly in Turkey and Northern Cyprus, where it has the status of an official language. In the Russian Federation there is little knowledge of Turkish, which seems to be the main reason for the growing demand for simultaneous interpreting. The purpose of the study is to conduct a linguistic analysis of Russian-Turkish and Turkish-Russian simultaneous interpretation, which will reveal the features of language structures that influence the choice of strategies and actions in the simultaneous interpretation process.